Paraphilia in Iraq, a general sketch A study in the sex clinic, at Al-Rashad teaching mental hospital - Shakir, Aziz Salim; Sarsam, Raghad Issa; Al-Dabagh, Hasan , Khalid; Marzook, Ahmed Abed (AL-Kindy College Medical Journal, 2013)
Background; paraphilias were studied in the sexclinic, at Al-Rashad teaching mental hospital, in theyears 2009-2010, a subject never touched before in thefield of psychiatry in Iraq.Aims of the study :1-to identify the prevalence of types and number ofparaphilias in those patients.2-to study the relationship of paraphilias withsociodemographic factors of the patients.Patients and methods; using the diagnostic criteria ofDSM IV TR, 52 patients from the outpatient sex clinicat Al-Rashad mental hospital, collected and studied (41males and 11 females).Results; the ratio of men to women was 3.7 : 1, themajority of our sample was in the age range of 21-30years (36.35%), with a limited(primary education)(about 48%) or no education(36.53%), not married as astatus was found in 48.07%, and low socio-economiclevel was in 57.69% of our sample. Exhibitionism wasfound in 19.23% of our sample, followed by zoophiliain males 17.07%, most of the disorders were foundexclusively in males, apart from masochism and someof the paraphilias not otherwise specified (NOS).Conclusion; paraphilia as a group of disorders, exist inour society, but lurks in the shadows of our strictcultural and religious societal background, they aresuppressed and stigmatized, for the majority of ourpatients were collected first in a private clinic, thendirected and encouraged to the sex clinic by theresearchers.